Traumatismos maxilofaciais decorrentes da prática de atividades esportivas: um estudo transversal - Rodrigo Caillaux Pereira (2020)
The search for an improvement in the quality of life resulted in a greater demand for the practice of sports activities worldwide. Although physical activities bring several benefits in the physical, psychological and social spheres, such practice increases the possibility of occurrence of maxillofacial injury as a result of sports practice, which can bring a series of losses to the athlete, resulting in emotional and functional consequences, decreased performance and financial losses. Given this scenario, the present research aims to carry out a cross-sectional, quantitative, descriptive and inferential analysis of the data obtained from medical records of patients seen, as a result of sports practices, in the Maxillofacial Surgery Sector of a Municipal Hospital in Belo Horizonte (MG). To this end, medical records of patients treated at the Hospital between January 2008 and May 2019 that involved maxillofacial injury and whose care was given as a result of sports activities were evaluated. The data were distributed in frequency and percentage tables. Independent variables such as sex, age, type of sport practiced, period of care, day of the week, month of occurrence, type of injury, location of the injury and type of treatment were associated with the type of maxillofacial injury that occurred. Statistical analysis was performed using SPSS (Statistical Package for the Social Sciences) 15.0 software for Windows using Pearson's chi-square test and Fisher's exact test, with a 5% significance level. 739 patients participated in the study. The occurrence of maxillofacial injury was more prevalent in adolescents and young adults (72.3%) males (91.9%), due to the practice of soccer (87.1%). The most prevalent type of injury was soft tissue (33.4%), with the middle third of the face (71.7%) and the central region (73.5%) being more frequently affected. The treatment performed on the patients attended was based, mostly, on a conservative procedure (84.2%). In addition, maxillofacial injury was associated with males (p = 0.045), the 10 to 29 years old age group (p = 0.028), soccer (p = 0.029), the middle third of the face (p < 0.001), the central region of the face (p = 0.044) and the conservative procedure (p < 0.001).